Changes in Chemical Composition of Betung Bamboo (Dendrocalamus asper) after Alkali Immersion Treatment under Various Immersion Times - Rio Ardiansyah Murda; Sena Maulana; Adesna Fatrawana; Silvia Uthari Nuzaverra Mayang Mangurai; Soleh Muhamad; Wahyu Hidayat; Yazid Bindar (Jurnal Sylva Lestari, 2022)
This research aimed to analyze the change in chemical composition of the betung bamboo (Dendrocalamus asper) strands after alkali immersion treatment under various immersion times. The bamboo culms were converted into strands with the target length, width, and thickness of 70, 25, and 0.5 mm, respectively. Strands were alkali immersion-treated with 1% NaOH solution for 1, 2, and 3 h. Preparation of powder for chemical component analysis refers to the Technical Association of the Pulp and Paper Industry (TAPPI) standard T 264 cm-07 regarding the preparation of wood test samples for chemical analysis. Structural and non-structural bamboo strand chemical components such as holocellulose, alpha-cellulose, hemicellulose, klason lignin, and extractives were analyzed. The results showed that alkali immersion treatment decreased the hemicellulose content from 21.55% before treatment to 20.30% after 3 h immersion. Thus, it changed the holocellulose and alpha-cellulose composition. Alkali immersion treatment also changed the extractive substances dissolved in cold water, hot water, 1% NaOH, and ethanol-benzene solution. The decrease in hemicellulose, molecular weight lignin, and extractive substances would be beneficial for bamboo-oriented strand board manufacture to improve strand adhesion, dimensional stability, mechanical properties, and durability against biological agents attack. Keywords: alkali immersion times, alkali immersion treatment, bamboo, chemical components, pre-treatment